Oral microbiome sequencing revealed the enrichment of Fusobacterium sp., Porphyromonas sp., Campylobacter sp., and Neisseria sp. on the oral malignant fibroma surface of giant panda - Wang, Xiaowan; Jing, Meiling; Ma, Qizhao; Lin, Yongwang; Zheng, Ting; Yan, Jiangchuan; Yun, Libing; Wang, Chengdong; Li, Yuqing (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Microbial community composition is closely associated with host disease onset and progression, underscoring the importance of understanding host–microbiota dynamics in various health contexts. Methods In this study, we utilized full-length 16S rRNA gene sequencing to conduct species-level identification of the microorganisms in the oral cavity of a giant panda (Ailuropoda melanoleuca) with oral malignant fibroma. Results We observed a significant difference between the microbial community of the tumor side and non-tumor side of the oral cavity of the giant panda, with the latter exhibiting higher microbial diversity. The tumor side was dominated by specific microorganisms, such as Fusobacterium simiae, Porphyromonas sp. feline oral taxon 110, Campylobacter sp. feline oral taxon 100, and Neisseria sp. feline oral taxon 078, that have been reported to be associated with tumorigenic processes and periodontal diseases in other organisms. According to the linear discriminant analysis effect size analysis, more than 9 distinct biomarkers were obtained between the tumor side and non-tumor side samples. Furthermore, the Kyoto Encyclopedia of Genes and Genomes analysis revealed that the oral microbiota of the giant panda was significantly associated with genetic information processing and metabolism, particularly cofactor and vitamin, amino acid, and carbohydrate metabolism. Furthermore, a significant bacterial invasion of epithelial cells was predicted in the tumor side. Discussion This study provides crucial insights into the association between oral microbiota and oral tumors in giant pandas and offers potential biomarkers that may guide future health assessments and preventive strategies for captive and aging giant pandas.